2018
DOI: 10.1021/acs.langmuir.7b03901
|View full text |Cite
|
Sign up to set email alerts
|

Gas Hydrate Formation Probability Distributions: The Effect of Shear and Comparisons with Nucleation Theory

Abstract: Gas hydrate formation is a stochastic phenomenon of considerable significance for any risk-based approach to flow assurance in the oil and gas industry. In principle, well-established results from nucleation theory offer the prospect of predictive models for hydrate formation probability in industrial production systems. In practice, however, heuristics are relied on when estimating formation risk for a given flowline subcooling or when quantifying kinetic hydrate inhibitor (KHI) performance. Here, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 28 publications
6
38
0
1
Order By: Relevance
“…Different researchers have proposed different denitions of hydrate induction time based on different experimental systems. [30][31][32][33][34][35] In this work, induction time is described from the macroscopic aspect, including critical nuclei stage and visible crystal stage. In other words, the induction time is determined by a start point and an end point that is easy to observe and characterized by the large amount of hydrate formation.…”
Section: Determination Of Induction Time Of Hydrate Formation In Ow mentioning
confidence: 99%
See 1 more Smart Citation
“…Different researchers have proposed different denitions of hydrate induction time based on different experimental systems. [30][31][32][33][34][35] In this work, induction time is described from the macroscopic aspect, including critical nuclei stage and visible crystal stage. In other words, the induction time is determined by a start point and an end point that is easy to observe and characterized by the large amount of hydrate formation.…”
Section: Determination Of Induction Time Of Hydrate Formation In Ow mentioning
confidence: 99%
“…Therefore, through sensitivity analysis, the system water content has the most signicant inuence on the induction period of CO 2 hydrate formation, liquid loading take the second place, mass ow rate next, and initial pressure on induction time the weakest. Moreover, establishing an induction time model for oil-water systems based on classic nucleation theories 34,35 will be the focus of next step work. According to the similarity criterion in uid mechanics, it is supposed that the ow and plugging phenomenon as well as mechanisms in the ow loop will have similarities with the industrial pipelines.…”
Section: Sensitivity Analysis Of Factors Affecting Hydrate Induction mentioning
confidence: 99%
“…Recently, May and co-workers (16,17) reported robust measurements of gas hydrate formation probability distributions using an improved technique based on a highpressure stirred automated lag time apparatus (HPS-ALTA), and compared their results with other experimental studies and the predictions of classical nucleation theory (CNT). (11) They found that careful nucleation rate measurements reported in the literature were broadly consistent, particularly those determined in well-mixed systems where the agreement was within a factor of three.…”
mentioning
confidence: 99%
“…( 16), em que valores menores no denominador 𝑉 tendem a aumentar o resultado final de %𝐸𝑅. Ainda, o perfil de formação naturalmente estocástico dos hidratos de gás acaba sendo uma problemática recorrente, especialmente em trabalhos experimentais, onde a necessidade de grande número de amostras é mandatória, pois a distribuição dos dados de formação tende a ser mais ampla que a predita [24]. Tabela 4: Erro relativo percentual para os dados experimentais de Vlasov [14] Outra vantagem de se utilizar um método computacional consiste na possibilidade de avaliação dos dados experimentais, sem a necessidade de preparação de novas amostras.…”
Section: Hidrato De Metanounclassified